Відновлення спеціальної працездатності спортсменів з ушкодженням передньої хрестоподібної зв’язки колінного суглоба - Ніканоров, Олексій Костянтинович; Nikanorov, Alexey (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті наведено дані щодо можливості застосування в програмах фізичної реабілітації спортсменів із пошкодженням передньої хрестоподібної зв’язки колінного суглоба пліометричних вправ, спрямованих на відновлення спеціальної працездатності. Мета роботи – провести аналіз та узагальнення науково-методичних даних із питань відновлення швідкісно-силових якостей у спортсменів після травм. Установлено, що в сучасних методиках фізичної реабілітації спортсменів з ушкодженнями опорно-рухового апарату не існує комплексних програм із використанням пліометричних вправ. Їх застосування сприяє ефективному відновленню швидкісно-силових якостей спортсмена, а також профілактиці рецидивних травм. The article provides us with data on the possibility of application of plyometric in complex programs of physical rehabilitation of athletes playing sports with damage to the anterior cruciate ligament of the knee joint to restore special performance. The aim of work was to analyze and summarize scientific and methodological information on the restoration of speed-strength qualities of athletes after injury. It has been established that the modern methods of physical rehabilitation of athletes with injuries of the musculoskeletal system are no comprehensive programs with plyometric exercises. Their use contributes to the effective recovery of speed-strength qualities of athlete, as well as the prevention of recurrent injuries. Using the plyometric training in rehabilitation activities in athletes playing sports is very important because it allows to restore a special performance and, above all, speed-strength qualities, specific to these sports. However, their use is only possible in the training period of physical rehabilitation, as it requires the mobilization of maximum motor function of the injured leg. Indication for the use of plyometric exercise is a complete absence of inflammation, restoration of motor function of the knee joint and its stability in the performance of functional tests and physical exercise. In this way, the inclusion of elements plyometric training in a complex of measures of physical rehabilitation allows to expand the range of tools and techniques of restoration of special working capacity of athletes playing sports at the expense of reconstruction and development of motor qualities specific orientation.
Restoration of Special Workability of Athletes with Damage to the Anterior Cruciate Ligament of the Knee joint
Keywords: спортсмен; колінний суглоб; пліометричні вправи; фізична реабілітація; передня хрестоподібна зв’язка; athlete; knee; plyometric exercises; physical rehabilitation; anterior cruciate ligament